Perancangan Sistem Informasi Pencatatan Surat Masuk Dan Surat Keluar Di Desa Tirta Kencana Berbasis Website - indramayu; Mira (Universitas Kristen Immanuel, 2023)
This study discusses the website-based information system for recording incoming and outgoing letters in Tirta Kencana Village. The aim of this research is to increase efficiency and transparency in the correspondence process at the village level. Manual recording processes that are prone to errors can be minimized, thereby increasing productivity and reducing the time needed to manage these letters. The results of this study indicate that the implementation of a website-based information system for recording incoming and outgoing mail in Tirta Kencana Village provides benefits in increasing efficiency, transparency, security, and communication in the correspondence process at the village level. This system can be a solid foundation for more effective correspondence management in the future.